Vancomycin pharmacokinetic parameters in patients undergoing hematopoietic stem cell transplantation. (January 2022) - Arjangpour, Samareh; Sadeghi, Kourosh; Solduzian, Mohammad; Mousavi, Seied Asadollah
Introduction: Current guidelines on vancomycin dosing lack specific recommendations about its dosing in hematopoietic stem cell transplant (HSCT) patients, the objective of the current study was to compare vancomycin pharmacokinetic variables in this population with those of general population. Methods: A prospective study was designed and the calculated parameters of vancomycin pharmacokinetic were compared with individualized parameters. Two trough levels before 4th and 5th doses and a peak level after the 4th dose, were taken. All patients received a dose of 15 mg/kg of vancomycin two or three times a day. Pharmacokinetic parameters were calculated using a one compartmental model. The association between different variables and of acute kidney injury (AKI) development and achievement of target levels were also evaluated. Results: A significant difference was observed between population Volume of distribution (Vd) and individualized Vd (mean 57.33 L vs 162.86 L, p value 0.019) and trough and peak levels (p values 0.0001 and 0.001; for mean trough and peak levels respectively). The achievement of the recommended trough levels and area under the concentration time curve per minimum inhibitory concentration (AUC24/MIC) was very low (5/71 and 24/71 patients respectively). No significant differences were observed between population and individualized clearance and rate of elimination of vancomycin (p values of 0.092 and 0.55 respectively). Concomitant receipt of cyclosporine was significantly related with development of AKI (p value 0.046). Conclusion: The dosing methods which use population-based pharmacokinetic variables does not result in desired therapeutic levels in HSCT patients, mainly because of larger vancomycin volume of distribution.